Light-based and cost-effective bioprinting of musculoskeletal GelMA constructs enriched with mesoporous bioactive glass nanoparticles - Sánchez-Rodríguez, Víctor Hugo; Pérez-Cortez, Juan Enrique; Gallegos-Martínez, Salvador; Chuck-Hernández, Cristina; Rodriguez, Ciro A.; Boccaccini, Aldo R.; Vázquez-Lepe, Elisa; Alvarez, Mario Moisés; Santiago, Grissel Trujillo de; Martínez-López, José Israel (International Journal of Bioprinting, 2024)
Bioprinting represents a promising technique for fabricating three-dimensional (3D) constructs with high-resolution and controlled architecture. However, many bioprinting technologies rely on expensive extrusion systems, which may compromise cell viability due to harsh processing conditions. This study presents the fabrication and characterization of musculoskeletal tissue in gelatin methacryloyl [GelMA]-based nanocomposite 3D constructs (comprising GelMA and mesoporous bioactive glass nanoparticles [MBGNs]) using a cost-effective, light-based bioprinting (LBB) system. We demonstrated that our strategy can produce high-resolution constructs (approximately 250 µm) while maintaining high cell viabilities (above 85%) for extended periods (weeks of culture). Furthermore, the nanocomposite constructs could facilitate the maturation of musculoskeletal tissue derived from C2C12 cells, as indicated by assessments of cell viability, elongation, and alignment over time. Our results suggested that the bioprinting approach outlined in this study allows for precise control of architecture, while creating a conducive environment for cell growth and tissue formation. These findings also highlighted the potential of the proposed LBB system to advance musculoskeletal tissue engineering for regenerative medicine applications.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Bioactive glass; Bioprinting; GelMA; Light-based bioprinting; Mesoporous bioactive glass nanoparticles; Musculoskeletal tissue